Islamic Film and Pierce’s Semiotic Theory - Kusuma, Dimas Yuda; Alfarisy, Fitri (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2025)
This study aims to determine how a film is represented through various aspects contained within it so that it can be categorized as an Islamic film. The definition and criteria for a film to be considered an Islamic film are still debated and require analysis to determine its category. This study uses Peirce's semiotics theory, which explains three important aspects of semiotics known as the triadic model: Representamen, Object, and Interpretant. Qualitative descriptive analysis was employed in this study using the non-participant observation method, involving repeated viewings of the film used as the data source. The study presents data from the analysis conducted through the audio and visual elements of the Islamic film. The results of the study indicate that a film is considered an Islamic film if it has one main point, namely the story presented, along with supporting points such as the film poster, symbols, dialogue, and scenes depicted in it. This study expands the use of Peirce's semiotics theory, which was previously more commonly used to identify signs as interpretations of elements in films, into a tool for determining criteria for categorizing film genres.